Diagnosis and follow-up of posterior inferior cerebellar artery dissection complicated with ischemic stroke assisted by T1-VISTA: a report of two cases. Issue 1 (December 2016) - Ishitsuka, Koji; Sakaki, Yusuke; Sakai, Shota; Uwatoko, Takeshi; Aibe, Hitoshi; Ago, Tetsuro; Kitazono, Takanari; Sugimori, Hiroshi
Abstract Background Volume isotropic turbo spin-echo acquisition (VISTA) is a new method similar to the 3D black-blood imaging method that enables visualization of a intramural hematoma. T1-VISTA has recently been applied in the diagnosis of intracranial arterial dissection. However, the identification of an intramural hematoma in posterior inferior cerebellar dissection (PICA-D) by T1-VISTA has only rarely been reported. Case presentation We herein report two patients who suffered from PICA-D complicated with ischemic stroke. Initial magnetic resonance arteriography was not informative, however, T1-VISTA depicted high-intensity signal areas suggesting an intramural hematoma of PICA-D in both cases. The high-intensity signal areas gradually reduced and finally disappeared at 4 months and 5 months after the onset, respectively. Conclusion Our cases demonstrate that T1-VISTA was able to assist in the diagnosis and follow-up of PICA-D.